Ecos de uma história silenciosa : grupos de OASE da IECLB - Blind, Sisi (2009)
The silence and the daily space of the women actions are referentials of analysis in the understanding construction of the memory transmission and the religious identity of the groups of women of the Ordem Auxiliadora de Senhoras Evangélicas na Igreja Evangélica de Confissão Luterana no Brasil. Silence doesn t speak, it s not possible to translate it in words, but in actions it becomes word. The daily actions and the Faith Testimony of the OASE women in silence are indications of the social format of our partner-religious reality. The Thesis of silence that we support happens of the words of the proper protagonists of the action. This silence is not synonymous of absence or weakness. It is presence and also to be able. The net of being able is a web that spreads over all the society and nobody can escape of it. Also the OASE women in its centenarian silence exert the power. To analyze the webs of the power that are deeply lived in the daily relations of these protagonists is to look at to the particularity of the life. The attempt to dive in the daily one, to search the significant one of the invisible one is to recognize it as space, time and place of the rational and irrationals conflicts of our time, where are establish the production problems of the concrete life. In the nets of the daily one are the ties, bows to be tied or unfastened. It s in the daily space that we take care of the basic necessities of life. The practical of the care is an important referential of the women action. It happens in many spaces but it s in the kitchen that concentrates most part of the two actions, as in the daily domestic service as in the communitarian actions. The kitchen is the place that allows the access to the culture understanding, of the religious expression that defines the behavior and the form of how is understood the daily life and faith. The kitchen s space is the place of memory, of smells, of relations continuity. It s around the table that the communion is deeply lived. It is through the memory that the values of Faith are transmitted. Therefore, it s the memory kept by the mother that makes them belong to the religious universe of communion, testimony and service. The characteristic profile of this group has in the transmitted memory the link s construction. This also is the characteristic profile of the religious mobilization: the perpetuation of the memory as constructor of the religious continuity. It s the religious memory that conserves, reproduces and guarantees the permanence of a thought, of a confessional identity. We have in the group of the OASE women a valuable and proven potential of guard of the religious identity memory and the continuity of the same.